2017
DOI: 10.7860/jcdr/2017/26515.10170
|View full text |Cite
|
Sign up to set email alerts
|

New Vision for Improving the Oral Health Education of Visually Impaired Children- A Non Randomized Control Trial

Abstract: Introduction: Visually impaired people have poorer oral hygiene when compared to others. Therefore, there is a necessity for individual training by making awareness in oral care and plaque control so as to improve their oral hygiene. Aim:The aim of the present study was to assess the effectiveness of oral health innovative educative method among visually impaired children of Bengaluru city of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 7 publications
4
59
0
5
Order By: Relevance
“…57,58,70,71 The 66 included studies were published between 1964 and 2018, and 37 (56.1%) of them were published in the last decade (2008e2018) 1e3, 13,15,16,19e21,27,28, 30,32,33,35,39,40,43,46,51,54,62,65,69e71,73e75,78,82,83,85,89,91,96,98,104,110,111,124 ( Table 1). Most of the studies were conducted in the United States, 7,11,12,26,35,44,47,55e58,61,65,66,70e72,78,84,91,93,95,121 1 in Canada, 8 11 in Europe (i.e., United Kingdom, 50,108,119 Germany, 6 the Netherlands, 13,27,51,83,89 and Greece 69,82 ), 28 in Asian countries (i.e., Iran, 54 Turkey, 1,15,16,30,104,110,111,123,124 India, 20,21,28,39,40,43,46,62,74,75,90,96 Jordan, 2 Pakistan, 85 Japan, 97 Taiwan, 19 and Thailand 3,98 ), a...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…57,58,70,71 The 66 included studies were published between 1964 and 2018, and 37 (56.1%) of them were published in the last decade (2008e2018) 1e3, 13,15,16,19e21,27,28, 30,32,33,35,39,40,43,46,51,54,62,65,69e71,73e75,78,82,83,85,89,91,96,98,104,110,111,124 ( Table 1). Most of the studies were conducted in the United States, 7,11,12,26,35,44,47,55e58,61,65,66,70e72,78,84,91,93,95,121 1 in Canada, 8 11 in Europe (i.e., United Kingdom, 50,108,119 Germany, 6 the Netherlands, 13,27,51,83,89 and Greece 69,82 ), 28 in Asian countries (i.e., Iran, 54 Turkey, 1,15,16,30,104,110,111,123,124 India, 20,21,28,39,40,43,46,62,74,75,90,96 Jordan, 2 Pakistan, 85 Japan, 97 Taiwan, 19 and Thailand 3,98 ), a...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…57 Fourteen studies reported a cutoff criterion for visual acuity. 1,11,13,21,27,28,30,35,47,51,54,75,78,89 Slightly more often, studies reported the degree of visual impairment (e.g., severe visual impairment, legal blindness) or fulfillment of certain criteria for low vision (e.g., the criteria for low vision of the WHO or the ICD criteria). 1,6,16,20,39,40,44,50,56,62,69,75,90,93,96,104,110,111,121 In some cases, authors quantified the number of participants with a certain degree of visual impairment, that is, how many participants had visual impairment and how many participants were blind.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…When properly supervised, children with and without visual impairment both develop similar caries prevalence, thus highlighting the role of impairment in disease cycle and importance of supervision in its prevention 27 . Very few studies on visually impaired children have examined the improvement in oral health after educating these children through braille, models or audio aids [28][29][30] . The decrease in plaque scores over follow-up in the present study is in accord with another study 31 , wherein a decrease in mean plaque score from 1.30 AE 0.46 to 0.85 AE 0.40 was achieved over a 9-month period after implementation of an oral health education programme.…”
Section: Discussionmentioning
confidence: 99%